Clinical Impact of two Different Diagnostic Strategies in the First- and Second-Line Treatment of Locally Advanced or Metastatic EGFR-Mutated Non-Small Cell Lung Cancer - Gancitano, Giovanni; Ravasio, Roberto; Cattelino, Lorenzo; Di Procolo, Paolo; Cortinovis, Diego (Farmeconomia. Health economics and therapeutic pathways, 2020)
BACKGROUND: A histopathological and mutational diagnosis has become a priority in the correct choice of the most appropriate cancer therapy for NSCLC. In the absence of a molecular analysis, the therapeutic choice will be directed towards platinum-based chemotherapy, thus preventing, in the presence of a specific mutation, the benefits deriving from the administration of a target therapies (TT). AIM: the present analysis was carried out with the aim of estimating the clinical impact, expressed in terms of progression free survival (PFS), associated with the use of the combined strategy (tissue biopsy and liquid biopsy) or the tissue strategy in the EGFR+ mNSCLC population. METHODS: A pre-existing cost-consequence model was adapted to estimate the annual number of mNSCLC patients with or without the EGFR mutation in order to decide the oncological treatment to be administered in first (1L) or second line (2L). In 1L, against the presence of the EGFR mutation, the administration of a Tyrosine Kinase Inhibitor (TKI), such as osimertinib, gefitinib, erlotinib or afatinib, was considered; in the absence of the EGFR mutation, the administration of standard platinum-based chemotherapy was instead considered. With reference to 2L, in the presence of the EGFR T790M mutation, only osimertinib was considered. In the absence of the EGFR T790M mutation, the administration of the standard platinum-based chemotherapy was also considered. The PFS data associated with each of the drugs considered were extrapolated from the respective clinical studies. Key variables were tested in the sensitivity analysis. RESULTS: The adoption of the combined strategy (tissue biopsy and liquid biopsy), by virtue of a greater number of patients treated with TKIs, would make it possible to increase the average PFS in the range of 1.1-3,7 months in the 1L and by 1.4 months in the 2L. CONCLUSION: These results show how the adoption of a correct diagnostic strategy is critical in order to optimize the choice of the therapeutic path in the 1L and 2L of mNSCLC. The addition of the liquid biopsy to the classic diagnostic path (tissue biopsy) would in fact allow to obtain an increase in therapeutic efficacy (average PFS).